Evaluating the Impact of Community-Based Economic Empowerment on Poverty Reduction: Evidence from the Joint Business Group (KUBE) Program in Kebumen Regency, Indonesia - Aji Primanto; Linda Puspitasari (CV Putra Publisher, 2026)
Poverty remains a multidimensional development challenge that requires policy interventions extending beyond short-term economic assistance toward sustainable community empowerment. This study evaluates the impact of the Joint Business Group (Kelompok Usaha Bersama/KUBE) Program on poverty reduction in Kebumen Regency, Indonesia, by examining four evaluation dimensions: economic conditions, social relations, institutional capacity, and entrepreneurship. A quantitative evaluative approach employing a one-group pretest–posttest design was adopted. Primary data were collected through questionnaires administered to 28 KUBE beneficiaries selected using total sampling, while secondary data were obtained from relevant government documents. Data were analyzed descriptively to compare respondents' perceptions before and after program implementation. The findings indicate that the KUBE Program generated positive outcomes across all evaluation dimensions, with an overall implementation success rate of 85.7%. Entrepreneurship demonstrated the highest achievement, followed by institutional capacity and social relations, whereas economic conditions showed comparatively lower improvement. These findings suggest that the program more rapidly strengthens entrepreneurial motivation, social cohesion, and institutional capacity, while economic improvement requires a longer period because it depends on business development, market access, capital availability, and sustained mentoring. The study concludes that evaluating poverty alleviation programs should adopt a multidimensional perspective that incorporates economic, social, institutional, and entrepreneurial dimensions. Policy efforts should therefore prioritize continuous business mentoring, institutional strengthening, entrepreneurship development, and improved access to markets and financial resources to enhance the long-term effectiveness of the KUBE Program in reducing poverty